Speaking post-truth to power. (Economist, 2017)
The article discusses the U.S. President-elect Donald Trump's relationship with U.S. intelligence services, within the context of the latter's conclusion that Russia hacked into American political system to influence the U.S. 2016 presidential elections. It discusses the truthfulness and falsehoods in Trump's rhetoric on the intelligence agencies.